The effect of fish oil supplementation on fatigue perception following submaximal exercise during the COVID-19 pandemic - Nurussyariah Hammado; Etno Setyagraha; Fadra Naufal Rannu (UIR Press, 2023)
The pandemic of COVID-19 has created the